Lipschitz-Type and Bloch-Type Spaces of Pluriharmonic Mappings in a Hilbert Space - Yong Liu (Journal of Function Spaces)
We investigate some properties of pluriharmonic mappings in an infinite dimensional complex Hilbert space. Several characterizations for pluriharmonic mappings to be in Lipschitz-type and Bloch-type spaces are given, which are generalizations of the corresponding known ones for holomorphic functions with several complex variables.